International law and the protection of people at sea - Papanicolopulu, Irini (Oxford Oxford University Press, 2018)
From the actions of Somali pirates to the fate of asylum seekers in the Mediterranean, the rights of those at sea is of vital importance. The first book to comprehensively analyse the legal status of seafarers and sea-travellers, Papanicolopulu's timely text provides a compelling argument for the responsibility of the state to protect those at sea.
Introduction -- 1. People, the sea, and international law -- 2. Protection by the system and its regimes -- 3. The scope of state duties -- 4. The content of state obligations -- 5. From set of rules to legal regime.
Includes bibliographical references (pages 247-259) and index.
Keywords: Maritime law; International law and human rights; International law and human rights; Maritime law; 86.93 maritime law; 86.81 human rights; Law